Engaging Honduran Science Diasporas for Development: Evidence From Three Consolidated Networks - Bonilla, Kleinsy; Aquino Valle, Karina; Alvarez-Torres, Ramon; Ney Simons, Sara (Frontiers in Research Metrics and Analytics, 2022)
Honduras’ underdevelopment of the higher education system, national economic constraints, and low investment in science and technology (S&T) have created significant challenges in training, employing, and retaining its science workforce, resulting in what is known as “brain drain” in literature. There are no official statistics of Honduran scientists who have established their residency abroad, nor the Honduran scientific diasporas (HSD); however, various diaspora networks provide evidence of their existence and engagement in their home country. This study takes an empirical approach and explores experiences of networking and engagement of the HSD for the development of Honduras. Methodologically, a qualitative approach and a phenomenological design were used. The data was collected through documentary review and semi-structured interviews with key respondents from three identified HSD networks: Honduras Global (HG), the Organization of Women in Science for the Developing World, Honduras National Chapter (OWSD Honduras) and the Alumni Association of The Zamorano Pan-American Agricultural School (AGEAP-Zamorano). The holistic analysis of HSD´s engagement provides evidence of existing registry gaps. Neither the S&T agents nor the Honduras Foreign Policy have identified, mapped, and characterized Honduran scientists’ emigration patterns. Evidence suggests the willingness of the HSD to transfer knowledge, build bridges, and facilitate access to world-class research practices to their peers residing in Honduras and interact with broader sectors of the Honduran society.